Performance Enhancement by Using Wet Pad in Vapor Compression Cooling System - Zaidan, Maki H.; Ibrahim, Thamir K.; Alkumait, Aadel A. R. (ITB Journal Publisher, LPPM ITB, 2019)
Vapor compression cooling systems are widely used in hot and dry climates where the atmospheric temperature in summer reaches around 48 °C and the relative humidity can be below 20%. These cooling systems normally use environmentally friendly gases that do not harm the ozone layer. These systems work with high gas pressure, which consumes high energy and leads to a low coefficient of performance when compared to cooling systems that do not use an environmentally friendly gas. Theoretical and experimental studies have been conducted to find a suitable solution for the performance improvement of this type of cooling system. A possible solution is to lower the temperature of the air before it enters the condenser of the compression cooling system by passing it through a wet pad. The water evaporates due to the latent heat that is withdrawn from the wet pad. The air temperature is reduced to about 11 °C before it enters the condenser of the compression cooling system. This enhancement increases the cooling capacity of the vapor compression cycle by nearly 20% and increases the coefficient of performance by 15%, in addition to reducing the consumed electricity up to 15%. In conclusion, the proposed method of adding a wet pad can significantly enhance the performance of the vapor compression cooling system.